2010
DOI: 10.3390/en3101691
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Feedstock Conversion to Biodiesel via Ultrasound Technology

Abstract: Biodiesel has attracted increasing interest and has proved to be a good substitute for fossil-based fuels due to its environmental advantages and availability from renewable resources such as refined and waste vegetable oils. Several studies have shown that biodiesel is a better fuel than the fossil-derived diesel in terms of engine performance, emissions reduction, lubricity and environmental benefits. The increasing popularity of biodiesel has generated great demand for its commercial production methods, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Characterization of fly ash applied has been presented elsewhere [19]. The synthesized fly ash based zeolite Na-X catalysts (FA/Na-X) and the ion exchanged fly ash based zeolite X (FA/K-X) were characterized using the techniques described below.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of fly ash applied has been presented elsewhere [19]. The synthesized fly ash based zeolite Na-X catalysts (FA/Na-X) and the ion exchanged fly ash based zeolite X (FA/K-X) were characterized using the techniques described below.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The chemical composition, pore size distribution and ion exchange properties of zeolite are responsible for their versa-tile catalytic behaviour [10,11]. In a previous study by the authors, South African Class F fly ash loaded with potassium was used as a solid-base catalyst in the transesterification of sunflower oil to methyl esters to make a meaningful utilization of waste coal fly ash in biodiesel catalysis [19]. With the cost of synthesizing zeolite X from coal fly ash estimated to be almost one-fifth of that of producing commercial zeolites [7], the applications of the fly ash based hierarchical zeolites in biodiesel production is expected to be a low cost substitute for the commercially available zeolite X synthesized using conventional feedstocks.…”
mentioning
confidence: 99%
“…However, in the international market, the most technically feasible and commercialized alternative renewable fuel sources are biodiesel and bioethanol [7]. Several researchers found that oil from microalgae could be converted to biodiesel, by using supercritical and microwave methods [8], ultrasound methods [9,10], and direct transesterification (in situ) [11].The last method is one of the most promising technologies due to the simple process and lower energy consumption to produce biodiesel from microalgae [8,12,13]. By using In situ transesterification, energy consumption could be lowered due to bypassing lipid extraction.…”
Section: Biomass Conversionmentioning
confidence: 99%
“…The maximum yield of biodiesel that can be achieved was 90% at a temperature of 40 o C and at atmospheric pressure. Meanwhile, the use of ultrasound in the transesterification of waste cooking oil by Babajide et al [20] obtain a conversion of >90% at temperature of 30 o C and a pressure of 1 atm. However, weakness of ultrasound technology on the performance of this reactor are requiring quite long reaction time of about 30 minutes, the formation of glycerol as a byproduct and requiring a homogeneous alkaline catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced methods developed in the production of biodiesel were supercritical [16,17], microwave [18,19], ultrasonic [20,21], and plasma technology [22,23] methods. Some researchers studied the effect of the use of the reactor type to biodiesel yield as well as the process efficiency in biodiesel production [21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%